The federalization of corporate governance - Steinberg, Marc I. (New York, NY : Oxford University Press, 2018)
This work focuses on a very timely subject: the federalization of corporate governance. From both historical and contemporary perspectives, the text addresses the federalization of corporate governance in the United States.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 27, 2018).
Keywords: Corporate governance -- Law and legislation -- United States; Federal government -- United States; United States. -- Securities and Exchange Commission; Law; Laws of specific jurisdictions & specific areas of law